ADAPTASI DAN INTEGRASI BUDAYA LOKAL PADA BAHAN AJAR BAHASA INGGRIS OLEH GURU SEKOLAH MENENGAH DI TANIMBAR - Laratmase, Yesayas Palimau; Warouw, Maya P.; Rattu, Jultje A.J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ This research entitled â€œadaptasi dan integrasi budaya lokal pada bahan ajar bahasa Inggris oleh guru sekolah menengah di Tanimbarâ€ were focused to observe the use of English material adaptation by teachers in three secondary schools in Tanimbar, Maluku. The writer in this research used the theories from Richards (2007) and Cheng (2002) to be his main theories, where the typical of material adaptation that tried to be reached by teachers also came from those two theories, while the writer also read and learned some related research which have been done by Syahri and Susanti (2016) in Palembang and Warouw (2015) in Manado. In this research, the writer used some of data collection techniques that reliable to this research, namely; observations and interviews techniques. The finding shows that the mostly used technique is addition and it is practiced in the classroom spontaneously in order to meet the studentsâ€™ needs. Then, the mostly used local cultural content in teachersâ€™ practices is local folklores. Thhis local cultural content is used to develop studentsâ€™ interests in learning English and play an important role in the teaching and learning processes..Â Keywords:Â ELT Materials, Materials adaptation, local cultural contents.